Aplication Of Video Media To Increas Vocabulary Mastery In Grade 8 Student Of Mtsn 10 Padang Pariaman - Wella Oktavia; Fajriyani Arsya; Albaihaqi Anas; Eka Rizal (Innovative: Journal Of Social Science Research, 2023)
This research was prepared by Wella Oktavia, registration number: 2218011. Departement Arabic language education, college of education and educational sciences, syeikh Muhammad Djamil Djambek State Islamic University, Bukittinggi, with the topic: Aplication of video media to increas vocabulary mastery in grade 8 student of MTsN 10 Padang Pariaman”.Problems in teaching the Arabic language especially in understanding vocabulary. Students find it difficult to memorize vocabulary and their vocabulary is very little. This is due to the way the teacher presents the same material for years, so that students get bored easily. The purpose of this thesis is to illustrate the application of the video method to incrase vocabulary proficiency to increase proficiency with video media to increas vocabulary mastery in grade 8 student of MTsN 10 Padang Pariaman.The result of the research was the use of video to increase vocabulary mastery, and the author taught this video through training and the blackboard. The author used the experimental research to discover an increase in vocabulary mastery. As for the data collection method it is the questionnaire and the use of research analysis as a selection rule. The researcher came to the conclusion that using the model of give and take, you can increas vocabulary mastery in grade 8 student of MTsN 10 Padang Pariaman.